2006
DOI: 10.1002/edn.50
|View full text |Cite
|
Sign up to set email alerts
|

How diabetes and insulin therapy affects the lives of people with type 1 diabetes

Abstract: Background: Management of type 1 diabetes places a considerable burden upon patients in terms of frequent insulin injections and blood glucose monitoring. Aims: Patients' fears and thoughts concerning diabetes and treatment were explored in two focus groups. The features of insulin therapy most likely to influence treatment preferences of type 1 patients were investigated. These features would then be used to inform a quantitative patient preference study using a discrete choice experiment. Method: This qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…These lifestyle changes include diet modification, blood glucose monitoring and insulin administration (Golden , Goldbeck , Nafees et al . , Mednick et al . , Varni et al .…”
Section: Introductionmentioning
confidence: 99%
“…These lifestyle changes include diet modification, blood glucose monitoring and insulin administration (Golden , Goldbeck , Nafees et al . , Mednick et al . , Varni et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that the fear of nocturnal hypoglycemia is substantial for people with diabetes 4,12,14,15 . Nonsevere nocturnal hypoglycemic events (NSNHEs) are also common among people with diabetes 16,17 , and it has been observed that, of all the issues that cause anxiety among individuals with diabetes, patients have reported being most fearful of nocturnal hypoglycemic events 18 .…”
mentioning
confidence: 99%
“…For this reason, methodological recommendations on using focus groups in the health care context are quite rare, and researchers rely mainly on general advice from the social sciences (e.g., Krueger, 1988; Morgan, 1993; Morgan & Krueger, 1998; Stewart et al, 2007). Even though focus groups have been used in a great variety of health research fields, such as patients’ treatments and perceptions in the context of specific illnesses (rheumatoid arthritis: for example, Feldthusen, Björk, Forsblad-d’Elia, & Mannerkorpi, 2013; cancer: for example, Gerber, Hamann, Rasco, Woodruff, & Lee, 2012; diabetes: for example, Nafees, Lloyd, Kennedy-Martin, & Hynd, 2006; heart failure: for example, Rasmusson et al, 2014), community health research (e.g., Daley et al, 2010; Rhodes, Hergenrather, Wilkin, Alegría-Ortega, & Montaño, 2006), or invention of new diagnostic or therapeutic methods (e.g., Vincent, Clark, Marquez Zimmer, & Sanchez, 2006), the method and its particular use in health research is rarely reflected. Methodological articles about the focus group method in health care journals mainly summarize general advice from the social sciences (e.g., Kingry et al, 1990; Kitzinger, 1995, 2006), while field-specific aspects of the target groups (patients, doctors, other medical staff) and the research questions (not only sociological but often also medical or technical) are seldom addressed.…”
mentioning
confidence: 99%